Perspectives of Systems Informatics 7th International Andrei Ershov Memorial Conference, PSI 2009, Novosibirsk, Russia, June 15-19, 2009, Revised Papers - Pnueli, Amir; Virbitskaite, Irina; Voronkov, Andrei (Theoretical Computer Science and General Issues, 2010)
This book contains thoroughly refereed and revised papers from the 7th International Andrei Ershov Memorial Conference on Perspectives of System Informatics, PSI 2009, held in Akademgorodok, Novosibirsk, Russia, in June 2009. The 26 revised full papers and 4 revised short papers presented were carefully reviewed and selected from 67 submissions. The volume also contains 5 invited papers covering a range of hot topics in system informatics. The papers address all current aspects of theoretical computer science, programming methodology, and new information technologies, which are among the most important contributions of system informatics.